Formation of the underground movement in the Northern Crimea (1941–1943) - Vyacheslav Aleksandrovich Ivanov (Вестник Майкопского государственного технологического университета)
The steppe part of Crimea occupies two thirds of the total area of the peninsula. In the east, north and west it is surrounded by the Black Sea, the Gulf of Sivash and by the Sea of Azov, from the south – by the third ridge of the Crimean Mountains. The natural and geographical conditions of this region did not allow the guerrilla struggle against the German-Romanian invaders to be launched here, so it was limited to conducting intelligence activities, sabotage and propaganda by various patriotic underground organizations.In the Russian historiography, which studies the problems of anti-fascist Resistance on the territory of Crimea, unfortunately, a false stereotype has developed about the absence of underground work in the north of the peninsula.The purpose of the article is to dispel this myth, based on previously unpublished documents from: the funds of the municipal archive of the Administration of the Razdolnensky district, the State Archive of the Republic of Crimea and the Yalta Historical and Literary Museum. The research methods used are source studies, historical and typological, retrospective, statistical and biographical.In the course of the research, the author has identified previously unpublished materials about the activities of underground fighters on the territory of the Akh-Sheikhsky, Larindorfsky, KrasnoPerekopsky districts of the Crimean ASSR. The contribution of underground fighters to the common cause of the anti-fascist struggle has been noted, as well as the creation of conditions for the successful liberation of the peninsula from the German-Romanian occupation in the spring of 1944.